Born to run out of COVID-19: what gives us wings - Filipas, L.; La Torre, A.; Luzi, L.; Codella, R. (2020)
A pandemic called COVID-19 has spread worldwide in the first months of 2020. Several measures have been taken by mostly affected countries to contain the virus outbreak, from social distancing to closing social and commercial activities. Also, sports dynamics has been dramatically impacted by this pandemic, with training and competitions cancelled and no clear hypotheses on the expected restart dates. The International Olympic Committee even postponed Tokyo 2020 Olympics to 2021, with lots of consequences on athlete's preparation and mental focusing. Long-distance runners have seen cancelled or postponed all the spring races, included the Major Marathons, and associated economic sequalae are real. This pandemic could potentially have a huge impact not only on elite athletes' preparation for the Olympics, but also for global health. In fact, the impossibility to engage in regular activities (e.g., school, work, fitness facilities) and utilize community resources (e.g., parks, playgrounds, walking trails) have caused a sharp reduction in the levels of physical activity, and has upended western societies lifestyles. In turn, this may result in a substantially increased risk of developing cardiovascular and metabolic diseases. Indeed, physical activity is associated with reduced risk of mortality and incident cardiovascular and metabolic diseases in all regions of the world, with no indication of a ceiling effect for higher doses. Therefore, the scientific community rated physical activity as a low-cost approach to reducing deaths and cardiovascular disease that is applicable globally with potential large impact (1).